Монгол тоглоомын соёл хийгээд тэнгэр, лус савдгийн шүтлэг: Rituals of Mongol games and worship of spirit masters of heaven, earth and water - Г., Нандинбилиг (Mongolian Studies, 2023)
Archaeological findings show that Mongol traditional games are derived from tangible cultural heritage; they dictate worship and belief in spiritual and everyday matters through taboos and symbolic imagery from the games. Therefore, games are valuable objects of research in further understanding Mongol culture. 1. Mongol games are valuable objects of research, preserving traditional beliefs about taboo and magic, and their symbolic imagery shows belief in heave and worship of deities and spirit lords of land and water; 2. The cult of tenger 'heaven' has an observable influence on games through patterns, images and cattle marking; 3. It is evident from the customs of some Mongol games that Mongolians represented the invisible deities not with anthropomorphic drawings, but symbolically through patterns and shapes.